An Alkaline Protease-Digestion of Silkworm Powder Enhances Its Effects Over Healthspan, Autophagy, and Mitochondria Function in a Rotenone-Induced Drosophila Model - Mai, Linh Xuan; Kang, Sang-Kug; Jo, You-Young; Nguyen, Phuong; Kim, A-Young; Kim, Kee-Young; Kim, Nam-Suk; Koh, Young Ho (Frontiers in Nutrition, 2022)
Background Recent studies have reported that steamed and freeze-dried mature silkworms, also known as HongJam, have various health-promoting effects. Objective The goal of this study was to elucidate changes in the various health-promoting effects of HongJam, after its digestion with a food-grade protease. Materials and Methods We examined whether healthspan-promotion and rotenone-induced loss of motor-control prevention effects were enhanced in Drosophila fed with food-grade alkaline protease-digested HongJam compared to those fed with non-digested HongJam. The differences in mitochondrial functions, chemical susceptibilities, and activations of signal transduction pathways between Drosophila supplemented with various feed were examined to elucidate the molecular and biochemical basis of healthspan-promotion and locomotor-improvement effects of protease-digested HongJam. Results We first found that the healthspan-promotion effect of HongJam digested with a food-grade protease was different depending on the silkworm variety used for its production. Digestion with food-grade protease into White-Jade HongJam (WJ) as prepared from the White-Jade silkworm variety that spins white cocoons did not enhance its functionality. However, compared to Golden-Silk HongJam (GS), a food-grade protease-digested Golden-Silk HongJam (GSD) produced from the Golden-Silk silkworm variety that spins yellow cocoons, it further promoted the healthspan in a Drosophila model. By conducting a series of studies to reveal the molecular and biochemical basis for healthspan-promoting effects, we found that GS and GSD similarly enhanced mitochondrial activity, but GSD activated autophagy signaling more than GS. In addition, GSD feed (GSDf)-, GSD supernatant feed (GSDsupf)-, and GSD precipitate feed (GSDprecf)-reared Drosophila were also found to have increased resistance to an autophagy inhibitor compared to that of normal feed- or GS feed-reared Drosophila. Furthermore, we found that the rotenone-induced loss of motor control prevention effect was superior for GSDsup compared to GS, GSD, or GSDprec. This result may have occurred because GSDsup has more phenolic compounds and antioxidant activities than other samples. Conclusion GSDsup contained more digested small peptides and free phytochemicals than other samples due to the digestion of proteins with a food-grade protease. Thus, GSDsup leads to further healthspan-promoting and locomotor-improvement effects than GS, GSD, or GSDprec.